Dermoscopic pattern of juvenile xanthogranuloma. - Becha, T.; Litaiem, N.; Mansour, Y.; Rammeh, S.; Zeglaoui, F. (European Journal of Pediatric Dermatology, 2018)
Juvenile xanthogranuloma (JXG) is a benign disorder classified within ‘non-Langerhans cell histiocytosis’ mostly observed in infancy and early childhood. The diagnosis is confirmed by histopathology. Dermoscopy is a helpful tool in the diagnosis of JXG especially in unusual presentations. We report a case of JXG showing the “setting sun” dermoscopic appearance of JXG and discuss the possible differential diagnosis that may mimic this dermoscopic appearance.